Producers and drivers of odor compounds in a large drinking-water source - Qiu, Pengfei; Zhang, Yuheng; Mi, Wujuan; Song, Gaofei; Bi, Yonghong (Frontiers in Ecology and Evolution, 2023)
Taste and odor (T&O) problems have been affecting drinking water safety. As a eutrophicated drinking water reservoir in Tianjin city, the Yuqiao Reservoir was threatened by 2-MIB and geosmin in recent years. In this study, quantile regression analysis and metagenome were used to quickly and accurately screen the producers and drivers of 2-MIB and geosmin in this reservoir. The mean concentrations of 2-MIB and geosmin in the four-year were 103.58 ± 128.13 ng/L and 14.29 ± 27.95 ng/L, respectively. 2-MIB concentrations were higher in summer and autumn, with a bimodal variation throughout the year. Geosmin concentrations showed a decreasing trend from year to year from 2018 to 2021. Metagenome revealed that Pseudanabaena sp. dqh15, Microcoleus pseudautumnalis Ak1609, Pseudanabaena limnetica, and Planktothricoides raciborskii were the 2-MIB-producers, while Streptosporangium caverna and Dolichospermum circinale were the geosmin-producers. This finding indicates that metagenome achieved higher resolution of taxonomic annotation than amplicons to identify odor-producers, which helps us to understand the main taxa of odor-producing microorganisms in Chinese water bodies and the genetic basis of odor compounds in microorganisms. Multivariate quantile regression analysis indicated Pseudanabaena sp. and CODMn were the best predictors of 2-MIB concentrations, temperature and CODMn were the most useful parameters for describing geosmin concentration change. 2-MIB concentrations increased with the increase of Pseudanabaena sp. cell density and CODMn. Geosmin concentrations were higher at harsh temperatures and increased with higher CODMn. CODMn was significantly and positively correlated with the biosynthesis of secondary metabolites synthesis and terpenoid backone biosynthesis pathway. Both quantile regression and metagenome results showed that CODMn was an important driver of odor compounds. Understanding the sources and drivers of odor compounds was useful for improving taste and odor problem management. This's the first time that the main odor-producing producer in water bodies have been resolved by microbial metagenomic functional gene prediction.